Islam and globalisation - Union Européenne des Arabisants et Islamisants. (Leuven)
xxxi, 610, [8] s.
Keywords: "This volume contains the Proceedings of the 25th Congress of the Union Européenne des Arabisants et Islamisants (Naples, September 8-12, 2010) on Islam and Globalisation: Historical and Contemporary Perspectives. Besides a general view on globalisation (Agostino Cilardo) and the history of the Union on the occasion of its fiftieth anniversary (Urbain Vermeulen), the contributions concern History (Axel Havemann, Pasquale Macaluso, Antonino Pellitteri, Maria Giovanna Stasolla, Maria Vidyasova), Islam (Roswitha Badry, Marek M. Dziekan, Dmitry Frolov, Chistopher Melchert, Katarzyna Pachniak, Orsolya Varsanyi), Islamic Law (María Arcas Campoy, Reiner Brunner, Ana María Carballeira Debasa & Camilo Álvarez De Morales, Agostino Cilardo, Vasco Fronzoni, Wilferd Madelung), Literature & Linguistics (Abdessamad Belhaj, Julia Bray, Hélène Condylis, Francesca Maria Corrao, Adelya Gaynutdinova, Ali Kadem Kalati, Vladimir Lebedev, Ewa Machut-Mendecka, Mariangela Masullo, Barbara Michalak-Pikulska, Christina Ossipova, Arie Schippers, Krystyna Skarzynska-Bochenska, Ludmila Torlakova, Urbain Vermeulen, Monika Winet), Travel (Oriana Capezio, Roberta Denaro, Maria Grazia Sciortino, Richard Van Leeuwen), Philosophy & Science (Carmela Baffioni, Daniel De Smet, Montse Díaz-Fajardo, Paulina B. Lewicka, Miklós Maróth, Juan Martos Quesada & María del Carmen Escribano Ródenas, Antonella Straface, Johannes Thomann), Art (Vincenza Grassi, Eva-Maria von Kemnitz)." --